Knowledge brokers as agents for change: the role of lived experience and translational research in breaking intergenerational cycles of offending - Williams, Corrie (Frontiers in developmental and life-course criminology, 2024)
Transforming Corrections to Transform Lives (TCTL) is an innovative collaboration between researchers, mothers with lived experience of incarceration, stakeholders in both the government and non-government sectors, and philanthropy. The project aims to understand and create the conditions necessary for incarcerated mothers and their children to thrive. In this chapter, we describe how the TCTL project navigated the power structure of prisons by using a co-creation process, where the researchers and mothers involved in the project became “knowledge brokers.” Co-creation is a participatory research approach in which the end-users of services or programmes play an active role in their conceptualisation. While co-creation methods have been applied in fields such as health and public policy, they are less common in criminology, particularly in the correctional context. This is because co-creation aims to address power imbalances by enabling collaboration outside of the usual exchanges between researchers, service providers, and service users. In a prison setting, where the autonomy of service users is restricted and their involvement in the process of incarceration is involuntary, this can be challenging. Through knowledge brokering, the TCTL project was able to bridge power imbalances and establish conditions for meaningful impact. These conditions were reciprocity, collaborative inquiry, visible change, and sufficient allocation of resources. Our approach shows how co-creation can support developmental and life-course criminologists to move beyond traditional approaches to create social benefit. By describing our approach, we provide a blueprint for conducting translational research with and designing programmes for vulnerable populations and the systems in which they are embedded.